A Blueprint for Strengthening Food System Resilience in West Africa: Regional Priority Intervention Areas - Food and Agriculture Organization of the United Nations; World Bank (2021)
This report was inspired by the 2019 Kigali African Food Security Leadership Dialogue (AFSLD) that called for joint action to tackle the African Food Security challenges. ECOWAS, CILSS, CORAF, Consultative Group on International Agricultural Research (CGIAR) Research Program on Climate Change, Agriculture and Food Security (CCAFS), and the World Bank provided overall leadership for the process and analysis that underpins this report. Wageningen University prepared a background paper as input to the report. The information presented in this report represents a synthesis of the analysis of relevant secondary data and information as well as interviews with over fifty West African experts working on the food systems’ issues presented in this document. Findings from the draft report were presented and discussed in a four-day virtual conference with over 300 West African actors working in diverse areas of the food system. The results of this conference, together with detailed comments from all the relevant partners associated with the report, guided the revision process and production of this final report.